2003
DOI: 10.1038/nature01529
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional structural dynamics of myosin V by single-molecule fluorescence polarization

Abstract: The structural change that generates force and motion in actomyosin motility has been proposed to be tilting of the myosin light chain domain, which serves as a lever arm. Several experimental approaches have provided support for the lever arm hypothesis; however, the extent and timing of tilting motions are not well defined in the motor protein complex of functioning actomyosin. Here we report three-dimensional measurements of the structural dynamics of the light chain domain of brain myosin V using a single-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
416
2
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 448 publications
(445 citation statements)
references
References 42 publications
22
416
2
1
Order By: Relevance
“…17,18 This domain likely acts as a lever arm that amplifies small nucleotidedependent conformational changes in the motor domain to a large displacement. 19,20 Myosin V walks toward the plus end of actin by taking ∼37 nm steps per ATP hydrolyzed. 21,22 Myosin V transports a wide variety of cargo including pigment granules, membranous organelles and secretory vesicles in vertebrates, and mRNA in yeast.…”
Section: Molecular Motorsmentioning
confidence: 99%
“…17,18 This domain likely acts as a lever arm that amplifies small nucleotidedependent conformational changes in the motor domain to a large displacement. 19,20 Myosin V walks toward the plus end of actin by taking ∼37 nm steps per ATP hydrolyzed. 21,22 Myosin V transports a wide variety of cargo including pigment granules, membranous organelles and secretory vesicles in vertebrates, and mRNA in yeast.…”
Section: Molecular Motorsmentioning
confidence: 99%
“…A crystal structure and electron micrographs have suggested the lever-arm tilts in conjunction with ATP hydrolysis cycle 12,13 , leading to the model assumes that the 'lever-arm swing' is the dominant process for force generation 14,15 . However, recent single-molecule nano-imaging and high-speed atomic force microscopy (AFM) have revealed that the two head domains alternately step 72 nm (hand-over-hand mechanism) [16][17][18] by combining the lever-arm swing 19 by the lead head with a 'diffusional Brownian search' by the rear head 17,20 . In general, the lever-arm swing is responsible for force generation and triggering the Brownian search following detachment of the rear head.…”
mentioning
confidence: 99%
“…Based on a ''lever-arm tilting model'' (6), it has been proposed that the tilting of the long neck domain of the attached leading head biases Brownian motion of the trailing head forward (7). Recently, it was demonstrated by using a single-molecule f luorescence polarization technique that the orientation of f luorophores on calmodulin light chain attached to the neck domain of myosin-V indeed alters before and after mechanical steps (8). This finding is consistent with the lever-arm tilting model.…”
mentioning
confidence: 99%